Pengaruh Produk Bundling dan Diskon terhadap Keputusan Pembelian pada Pengguna Produk Skincare The Originote di Kota Gorontalo - Mandiri, Jihan Asmita; Ismail, Yulinda L.; Ramlan Amir Isa (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find out how much influence product bundling and discounts have on purchasing decisions for users of The Originote skincare products in the city of Gorontalo. This type of research uses quantitative methods, by distributing questionnaires to 100 respondents, the analysis used in this research uses multiple linear regression analysis. The results of the research show that, partially, the Product Bundling variable has a positive and significant effect on purchasing decisions with a significance level of 0.000 < 0.05 and a value of tcount > ttable, namely 3.654 > 1.660; Partially, the Discount Variable has a positive and significant effect on purchasing decisions with a significance level of 0.000 < 0.05 and a value of tcount > ttable, namely 4.189 > 1.660; and simultaneously the Product Bundling and Discount variables have a positive and significant effect on Purchasing Decisions with a significance level of 0.000 < 0.05 and a value of fcount > ftable, namely 25.054 > 3.090. The coefficient of determination R square is 0.341, which means that the percentage contribution of the influence of product bundling and discounts on purchasing decisions for users of The Originote skincare products is 34.1%, while the remaining 65.9% is explained or described by other variables not included in this research model.